Bridging students: successful transition from high school to college - Tang, Yee Voon *; Wong, Shae Lynn * (Sunway College Kuala Lumpur, 2015)
38 | P a g e BRIDGING STUDENTS – SUCCESSFUL TRANSITION FROM HIGH SCHOOL TO COLLEGE Tang Yee Voon and Wong Shae Lynn Sunway College Johor Bahru (MALAYSIA) yeevoont@sunway.edu.my, wongsl@sunway.edu.my +607-3596880 Abstract Transitioning from secondary school to college is an important developmental milestone that holds the potential for personal growth and behavioral change (Fromme, 2008). It involves changes in roles, additional challenges and responsibilities, be it academic or social (Conley et al., 2014). However, secondary school students often enter college unprepared for what is expected of them because their high school experiences often fail to prepare them for postsecondary education (Bangser, 2008). Key stressors for college students include personal freedom, college instructors and instructions, programme structures as well as testing and grades (Johnston, 2010). In addition to the stressors, students are not equipped with the skills required for successful college transition. These skills include academic skills, self-understanding (metacognition), selfadvocacy, executive function, motivation and confidence, key cognitive strategies and key knowledge about post-secondary education (Johnston, 2010; Landmark College, 2009). This paper embarks on a study specifically sought to identify transitional barriers faced by postsecondary students who are enrolled in the Pre-University programmes at Sunway College Johor Bahru. The outcome would also highlight the inadequacies of their pre-college preparation years and their lack of crucial skills to survive the college years. It is our hope that through this effort, we are able to establish approaches to support students in making a successful transition from high school to college. Successful transition is imperative because the benefits of postsecondary education are compelling. For an individual, this means getting jobs with higher wages and career advancement opportunities. For the country, this means a productive workforce and international competitiveness. Hence, successful transition to college should be a challenge shouldered by all parties, including policy makers, teachers and parents.